Model to Reduce Delays in Natural Gas Installation Works by Applying Lean Tools - Morales-Chuquihuanga, Fiorella (2023)
The construction industry is one of Peru's most relevant investment and production sectors, as it contributes to the economy and helps generate jobs and rent for the population. However, statistical research shows that 50.1% of the entire industrial sector reports not storing their materials. The remaining percentage do not use inventory management techniques, resulting in a great shortage of materials in their production. These incidents cause companies in the construction sector to generate delays in the completion of the works, preventing them from meeting the projected demand and causing severe economic losses for the companies. In this sense, to address the problem posed, a solution model was developed with lean tools: standardization of work, adjusted forecasting of demand, inventory management, approval, and homologation of suppliers. It is worth mentioning that the company under study initially obtained a total of 11% delay in the works. However, due to the implementation of the improvement model, a decrease of 6% was obtained due to scheduled replenishments, accurate demand forecasts, satisfied purchase orders and on-time delivery of materials. In conclusion, with this new solution, it is sought that similar companies can provide their services without presenting non-compliance in their work, generating an important level of competition in the market.